Updated insights into adverse events associated with mepolizumab: a disproportionality analysis from the FDA adverse event reporting system database - Lin, Shan; Luo, Dachen; Gong, Zonglian; Zhan, Qingyuan (Frontiers in Medicine, 2024)
Background: Mepolizumab, a monoclonal antibody targeting interleukin-5, is used to treat severe eosinophilic asthma and other eosinophilia-related conditions. Given its growing use, there is a pressing need for the latest data to improve the understanding and management of its adverse events (AEs). This study aimed to investigate the safety of mepolizumab by analyzing the pharmacovigilance database of the US Food and Drug Administration.The AE signals associated with mepolizumab from 2015 to 2024 were analyzed and the correlations using reporting ratios (RORs) quantified. Subgroup analyses were conducted to understand AEs in individuals ≤18 years of age. We also used time-to-onset (TTO) analysis to examine AE occurrence patterns.In total, 82,478 AE reports linked to mepolizumab therapy were included.Our analysis, involving 24,156 patients, revealed a predominance of female patients, with the highest incidence of AEs occurring in those aged 18-65 years.Disproportionality analyses revealed significant signals across various system organ classifications (SOCs), most prominently respiratory, thoracic, and mediastinal disorders (ROR=5.12, 95% confidence intervals [CI] 5.03-5.21), infections and infestations (ROR=1.86, 95% CI 1.81-1.90), and immune system disorders (ROR=1.14, 95% CI 1.08-1.21). The highest ROR was found for asthma crisis (ROR=104.90, 95% CI 95.31-115.44) at the preferred term (PT) level, and the other notables were coronavirus infection (ROR=7.33, 95% CI 6.05-8.88) and coronavirus disease 2019 . A subgroup analysis of patients ≤18 years old identified four significant SOC signals, with the highest ROR in respiratory, thoracic, and mediastinal disorders (ROR=5.28, 95% CI 4.17-6.68). PT analysis revealed significant AEs, such as wheezing, bronchospasm, and chest discomfort. TTO analysis revealed that 18.5% of AEs occurred within the first 30 days of treatment. The Weibull shape parameter indicated an "early failure-type" pattern for mepolizumab-associated AEs, underscoring the need for vigilant monitoring during the initial stages of therapy.Our study highlights the importance of post-market surveillance for monitoring the safety of mepolizumab, which revealed significant AE signals, particularly for respiratory diseases, infections, and immune system complications.The association with opportunistic infections, including COVID-19, highlights the need for vigilant surveillance and further research.